Analisis Business Model Canvas Pada Hawaii Swalayan Rumbai - Abdul Hamid; Fitriani Muttakin; Muhammad Ridho Anugrah; Nanda Nazira; Nola Ardelia Al Qadr; Rifky Ramadhan (UIN Sultan Syarif Kasim Riau, 2022)
Business development in Indonesia is progressing well. One form of business in Indonesia is the retail business which plays an important role in the flow of goods. Retail business growth is increasing every month so that competition among retail businesses is also increasing. Business efforts in maximizing profits are modeled in the Business Model Canvas (BMC). This study analyzes the BMC of the Hawaiian Rumbai supermarket retail business, which then analyzes the Strength, Weakness, Opportunity, and Threat (SWOT) of each BMC element. SWOT analysis of the elements of Customer segments, Value Propositions, Channels, Customer Relationships, Revenue Streams, Key Resources, Key Activities, Key Partners, and Cost Structures in BMC resulted in a new BMC modeling that focuses on daring buying and selling aspects, membership systems and opening up investment opportunities in order to expand the market and reduce initial capital costs.